Tafsir Religiositas Cinta terhadap Buku Puisi Ijinkan Aku Mencintaimu Karya Abdul Wachid B.S. - Riana Anjarsari Riana Anjarsari (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The discussion of the religiosity of love leads to the appreciation of love which is based on religious values ​​in an exoteric depth dimension. The thought of the religiosity of love questions an appreciation of love so that love relationships are colored with sincerity. In the book of poetry "Ijinkan Aku Cintamu" by Abdul Wachid BS, it is clear that love is positioned as a union between human relationships with other humans, human relationships with themselves, human relationships with the environment, and human relationships with God. This love is based on the five theories of Erich Fromm's love which were studied with the hermeneutic study of Paul Ricoeur's interpretation. This study aims to describe (1) the metaphor and symbol of the interpretation of the religiosity of love (2) the interpretation of the religiosity of love. The population in this study amounted to 57 poems, while the sample used was only 5 poems and there were 21 poems that became contextual poems. The data analysis technique used in this study led to descriptive explanations as a characteristic of qualitative research and used five stages in accordance with three methodological steps. Paul Ricoeur's interpretation of hermeneutics. The results of this study indicate that the metaphors, symbols, and interpretations of the religiosity of love in the poems contained in the poetry book Ijinkan Aku Cintamu by Abdul Wachid BS are very thick in each of his poems. The love contained in Abdul Wachid BS's poems in the poetry book Ijinkan Aku Cintamu is based on Erich Fromm's five theories of love, namely brotherly love (the poem “Catatan Pagi 1 Mei”), motherly love (the poem "Surat"), erotic love (the poem “Honey-Moon”), self-love (the poem “Burung”), and love of God (the poem”Nyanyian Cinta”